Integrated well of landfill conductance gas flowing back monitoring - SHI HUI; PAN JIANQIANG; LIU DEYUN; DING BAOMING; LI LIANG (2016)
The utility model discloses an integrated well of landfill conductance gas flowing back monitoring, include: the branch pipe constitutes and to be located the outer bypass of oozing the filter liquid discharging pipe of shaft, the liquid level detection table is connected in the end of branch pipe, the second valve, set up in in the branch pipe part, the compressed gas interface is located the branch pipe between liquid level detection table and second valve for insert compressed gas, and first valve, set up on oozing the filter liquid discharging pipe to be located the rear side of filtration liquid discharge direction. The foundation the utility model discloses filtration liquid liquid level detection can carry out indirectly. 本实用新型公开了种填埋气导气排液监测集成井，包括：支管，构成位于竖井外的渗滤液排放管的旁路；液位检测表，连接于支管的末端；第二阀门，设置于所述支管部分上；压缩气体接口，位于液位检测表与第二阀门间的支管上，用于接入压缩气体；以及第阀门，设置在渗滤液排放管上，并位于渗滤液排出方向的后侧。依据本实用新型可间接进行渗滤液液位检测。